Effect of exercise on multi-compartment lipid metabolism in murine models fed an obesogenic diet using non-targeted LC/MS - M. Gangadhara, Rachana; Gowda, Divyavani; B. Gowda, Siddabasave Gowda; Upadhyay, Gunjan; Chainani, Nikhil; Kain, Vasundara; V. Halade, Ganesh; Hui, Shu-Ping (Frontiers in Nutrition, 2025)
BackgroundChronic inflammation from obesogenic diets (OBD) disrupts lipid metabolism and contributes to non-communicable metabolic diseases. Exercise is a non-drug intervention that reduces inflammatory metabolic diseases by improving lipid metabolism. However, there are research gaps in understanding how the lipid metabolites are altered by exercise under an OBD.MethodsTwo-month-old male C57BL/6 J mice were fed a control (CON diet-Standard Lab Chaw-3.4%w/w Teklad Global #2918) or OBD for 10 months, then assigned to sedentary (Sed) or exercise (Exe) groups for 2 weeks. This study aims to examine changes in lipid metabolites in plasma, tissues, and feces of mice using untargeted liquid chromatography/mass spectrometry (LC/MS). Echocardiography was used to assess the impact of OBD on heart function.ResultsA total of 363 lipid molecular species were identified and characterized in the murine samples by retention time behavior and MS/MS spectral annotation. Multivariate analysis showed a distinct group separation between CON and OBD groups in both Sed and Exe groups. Phospholipids acylated with docosahexaenoic acid (DHA) are the key metabolites responsible for group separation in tissues and plasma, whereas in feces, glycerolipids, mainly monoacylglycerols. Lysophosphatidylethanolamine (LPE 22:5) was significantly upregulated in the liver, plasma, and left ventricle of the OBD mice in both Sed and Exe groups, contradictorily DHA containing phosphatidylglycerol [PG (22:6/22:6)] was significantly downregulated. Exercise modestly modulated the lipid profile under OBD, lowering plasma ceramides and partially reversing lipid alterations in feces. Interestingly, exercise combined with a control diet led to an increase in gut-microbiota-derived short-chain fatty acid esters of hydroxy fatty acids.ConclusionChronic OBD induces distinct lipid alterations across multiple biological compartments. Short-term exercise provides modest improvements, with stronger benefits when combined with a balanced diet.